2012
DOI: 10.1007/s10555-011-9344-6
|View full text |Cite
|
Sign up to set email alerts
|

EMT in carcinoma progression and dissemination: Facts, unanswered questions, and clinical considerations

Abstract: Over the past decade, much effort has been made to understand how cancers metastasize. In deciphering the metastatic process, a vast amount of work has focused on the role of the epithelial to mesenchymal transition (EMT), which, in experimental models, confers tumor cells with invasive and metastatic abilities, resistance to therapies, as well as cancer stem cell phenotype-properties that have a major impact on cancer prognosis. Searching "EMT and cancer" in PubMed retrieves thousands of original research art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 50 publications
1
64
1
2
Order By: Relevance
“…Additionally, we observed a significant decrease and increase in the expression of ERCC1 and p53, respectively, with the TNM stage of EC, which suggested ERCC1 and p53 as potential markers for the TNM stage of EC. EGFR overexpression was suggested to be associated with a number of cancers (Bastid, 2012); however, in this study, the expression of EGFR did not increase significantly with the TNM stage of EC, which suggested that the mechanisms of EC were unique, and that EGFR might be a key factor affecting this variation (Table 1). …”
Section: Association Between Ercc1 Egfr and P53 Expression And Clincontrasting
confidence: 62%
“…Additionally, we observed a significant decrease and increase in the expression of ERCC1 and p53, respectively, with the TNM stage of EC, which suggested ERCC1 and p53 as potential markers for the TNM stage of EC. EGFR overexpression was suggested to be associated with a number of cancers (Bastid, 2012); however, in this study, the expression of EGFR did not increase significantly with the TNM stage of EC, which suggested that the mechanisms of EC were unique, and that EGFR might be a key factor affecting this variation (Table 1). …”
Section: Association Between Ercc1 Egfr and P53 Expression And Clincontrasting
confidence: 62%
“…32,41 The agents tested in those studies were usually only for laboratory use. Recently, three COX-2 inhibitors have been reported to inhibit EMT in human bladder cancer cell lines in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, once malignant carcinoma cells have metastasized to secondary sites, they can apparently revert back to epithelial-like morphologies along with reexpression of epithelial markers, indicating that EMT has transient and potentially reversible characteristics (80,81). Although EMT changes have been associated with invasion and metastasis in animal tumors, there remains an ongoing debate on whether this phenomenon is truly representative of malignant pathways in human cancers (84). Indeed, Tarin (85) has argued that invasive cell phenotypes occur after normal tissues are damaged and during embryogenesis and that there is a lack of convincing pathologic evidence in humans that EMT occurs when carcinomas metastasize.…”
Section: Cell Membranes and The Invasive Phenotypementioning
confidence: 99%